1992
DOI: 10.1007/bf01923449
|View full text |Cite
|
Sign up to set email alerts
|

2-Hydroxy-5-methyl-1,4-benzoquinone from the salivary gland of the soldier termitesOdontotermes magdalenae

Abstract: Abstract. Attention is drawn to certain errors in our recently reported mass spectral study a of the salivary gland secretion from soldier termites of Odontotermes magdalenae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…It seems clear that soldiers of basal families (Mastotermitidae, Hodotermitidae, Archotermopsidae, Stolotermitidae, Kalotermitidae sensu [55] , lacking the frontal gland, rely only upon labial glands, while in more advanced families (Rhinotermitidae, Serritermitidae, Termitidae), having both glands, it is usually the frontal gland, which is the dominant defensive organ. The only exception occurs in soldiers of Macrotermitinae (Termitidae), in which enlarged labial glands [23] play a prime role [13] , [14] , [16] , [17] , [20] while the frontal gland produces small amounts of secretion with anti-healing properties [56] . In our study, the only identified defensive compound produced by the labial glands in soldiers having the frontal gland as a dominant defensive organ, is hydroquinone found in Coptotermes formosanus .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems clear that soldiers of basal families (Mastotermitidae, Hodotermitidae, Archotermopsidae, Stolotermitidae, Kalotermitidae sensu [55] , lacking the frontal gland, rely only upon labial glands, while in more advanced families (Rhinotermitidae, Serritermitidae, Termitidae), having both glands, it is usually the frontal gland, which is the dominant defensive organ. The only exception occurs in soldiers of Macrotermitinae (Termitidae), in which enlarged labial glands [23] play a prime role [13] , [14] , [16] , [17] , [20] while the frontal gland produces small amounts of secretion with anti-healing properties [56] . In our study, the only identified defensive compound produced by the labial glands in soldiers having the frontal gland as a dominant defensive organ, is hydroquinone found in Coptotermes formosanus .…”
Section: Discussionmentioning
confidence: 99%
“…production of the cement used in construction and the food for the dependent castes [4] , [11] . The function of the labial glands in soldiers was studied only in Mastotermes darwiniensis (Mastotermitidae) and several Macrotermitinae (Termitidae), in which they contribute to chemical defence by producing quinones [12] , [13] , [14] , [15] , [16] , [17] , mono- and sesquiterpenes, aromatic compounds or macrocyclic lactones [18] , [19] , [20] responsible for toxic, irritant, and congealing effects of the secretion released into the wound caused by mandibles (for review see [21] ). Other partially characterized-compounds (a protein, [16] ; a polysaccharide, [20] ) are expected to play the role of a stiffening agent.…”
Section: Introductionmentioning
confidence: 99%
“…strinati exudate (Figure 2c) has a molecular ion at m/z 136 and could possess either structure 9 or 7. However, the presence of the two fragments at m/z 54.0067 (22) and at m/z 54.0427 (23) (calculated mass 54.0470) indicate that two methyl substituents are on the same side of the benzoquinone, confirming structure 9. Benzoquinone 12 (Figure 2d), however, has fragments at m/z 54.0430 (23), indicating the presence of two methyl groups on C-2 and C-3, and at m/z 68.0229 (24) (calculated mass 68.0257), indicating the presence of a methyl group at C-5.…”
Section: Benzoquinones Identificationmentioning
confidence: 93%
“…They are known to be toxic and therefore are employed by beetles [17][18][19][20], earwigs [21], termites [22] and harvestmen [12,13] as a defence against natural predators. Additionally, their antimicrobial activity protects cockchafer larvae [23] and adult harvestmen [11] against pathogens, such as bacteria and fungi.…”
Section: Open Accessmentioning
confidence: 99%
“…Alternatively, interspecific variation in nest and cuticular microbial loads could be accounted for by species-specific differences in biochemical defenses, as suggested by Cruse (1998): species with more efficacious biochemical protection should have lower nest and cuticular microbial loads. Although glandular secretions and exudates are undoubtedly important for the control of infectious agents (Batra and Batra, 1966; 1973; Sannasi and Sundara Rajulu, 1967; Olagbemiro et al, 1988; Rosengaus et al, 1998, 2000), we believe that the discrepancy between nest and cuticular loads may provide a better measure of the impact of termite antibiotics on nest microbes. While the microclimatic conditions and other physical attributes of the nest may support high microbial activity, effective antimicrobial secretions should minimize cuticular loads despite the high encounter rate with microbes.…”
Section: Discussionmentioning
confidence: 96%